Temporal characteristics of respiratory syncytial virus infection in children and its correlation with climatic factors at a public pediatric hospital in Suzhou - Zhang, Xue-Lan; Shao, Xue-Jun; Wang, Jian; Guo, Wan-Liang (Journal of clinical virology, 2013)
Respiratory syncytial virus (RSV) is the most important viral pathogen in infants and children. It is important to analyze RSV epidemic patterns and related relevant factors in order to prevent further infections and related complications. To explore the relationship between RSV infection rate in hospitalized children from Suzhou area and climatic factors. 42,664 nasopharyngeal specimens from hospitalized children with acute respiratory infections were screened for RSV antigens using direct immunofluorescence. 472 RSV positive samples were randomly selected and performed real-time PCR to identify RSV subtype. Monthly meteorological data in Suzhou area was collected (average temperature, relative humidity, precipitation, total sunshine, and average wind speed) from 2001 to 2011. The relation between RSV infections and climatic factors was evaluated using correlation and stepwise regression analyses. The annual RSV infection rate in hospitalized children in Suzhou from 2001 to 2011 varied between 11.85% and 27.30%. The highest monthly infection rates occurred from November to April. The time interval from November to April was considered the infection season. Seasonal RSV infection rates from 2001 to 2010 were 40.75%, 22.72%, 39.93%, 27.37%, 42.71%, 21.28%, 38.57%, 19.86%, and 29.73%. The infection rate of any season was statistically different from the next season. There was no significant difference in RSV infection rates in the 2010–2011 and 2009–2010 epidemic seasons. Among the 472 randomly selected RSV positive samples, 412 were found to be RSV subtype A (RSV-A), while 60 subtype B (RSV-B). The monthly RSV infection rate was negatively correlated with monthly average temperature (r=−0.84), total sunshine (r=−0.47), precipitation (r=−0.31), relative humidity (r=−0.20), and average wind speed (r=−0.20), (P<0.05). Stepwise regression analysis showed monthly average temperature fit into a linear model (R2=0.64, P<0.01) with a regression coefficient of −1.52 (t=15.21, P<0.01). RSV infection in Suzhou occurred most frequently between November and April. The number of infections peaked every other year. Abnormally high infection rate in non-epidemic season only caused by RSV-A. Ambient temperature played an important role in the development of RSV infection.